The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jamasurg.2014.1332
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nocturia Severity in Men

Abstract: Neither race nor metabolic risk factors affect nocturia severity. In contrast, variables that denote nocturnal urine overproduction sharply discriminate the risk of nocturia severity and suggest that variable data may provide useful clinical correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Prior studies have found significantly increased risks for LUTS in Hispanic/Latino and African American descent adults regardless of gender or comorbidities. 2629 This association has not been previously noted in pediatric children.…”
Section: Discussionmentioning
confidence: 45%
“…Prior studies have found significantly increased risks for LUTS in Hispanic/Latino and African American descent adults regardless of gender or comorbidities. 2629 This association has not been previously noted in pediatric children.…”
Section: Discussionmentioning
confidence: 45%